Optimal sequence of adjuvant endocrine and radiation therapy in early-stage breast cancer – A systematic review. (September 2018) - McGee, S.F.; Mazzarello, S.; Caudrelier, J.M.; Lima, M.A.G.; Hutton, B.; Sienkiewicz, M.; Stober, C.; Fernandes, R.; Ibrahim, M.F.K.; Vandermeer, L.; Hilton, J.; Shorr, R.; et al.
Highlights: Clinical equipoise exists around the optimal timing of starting endocrine therapy in patients receiving post-operative radiation therapy. Theoretical concerns exist about the effects of concurrent endocrine therapy and radiation therapy. A systematic review was unable to confirm or refute whether or not these theoretical concerns actually exist in clinical practice. Larger, confirmatory trials are required. Abstract: Importance: Clinical equipoise exists around the optimal time to start adjuvant endocrine therapy in patients who will receive post-operative radiotherapy for breast cancer. Concerns continue to exist regarding potential reduced efficacy, or increased toxicity, when radiation, and endocrine therapy are administered concurrently. Objective: To perform a systematic review of studies comparing outcomes between sequential and concurrent adjuvant radiation and endocrine therapy in early-stage breast cancer. All modalities of radiation therapy were considered, and endocrine therapy could be either tamoxifen or an aromatase inhibitor. Outcomes of interest included; local, regional or distant recurrence, overall survival and treatment-related toxicities. Evidence reviewed: PubMed, Ovid Medline, EMBASE, and the Cochrane Central Register of Controlled Trials were searched from 1946 to December 2017. Two reviewers independently assessed each citation using the criteria outlined above. Study quality was assessed using the Cochrane Collaboration's tool for prospective studies, and the Newcastle-Ottawa scale for retrospective studies. Findings: Of 2137 unique citations identified, 13 met eligibility criteria. Eleven were unique studies (7569 patients), while 2 of the studies were updated analyses of previous studies. Studies evaluated the timing of adjuvant radiation, and tamoxifen (5 studies, 1550 patients), or aromatase inhibitors (6 studies, 6019 patients). We identified 1 complete randomized clinical trial (150 patients), and 5 retrospective studies (1580 patients), in addition to conference abstracts (5 studies, 5839 patients). Overall, none of the studies showed a significant difference in efficacy, or toxicity, with concurrent versus sequential treatment. However, given the significant heterogeneity of the study populations, it was not possible to conduct a meta-analysis. Conclusions and relevance: In the absence of high quality data, adequately powered randomized trials are required to answer this important clinical question.